Stark broadening parameters and transition probabilities of persistent lines of Tl II. Issue 1 (28th February 2018) - de Andrés-García, I; Colón, C; Fernández-Martínez, F
Abstract: The presence of singly ionized thallium in the stellar atmosphere of the chemically peculiar star χ Lupi was reported by Leckrone et al. in 1999 by analysis of its stellar spectrum obtained with the Goddard High Resolution Spectrograph (GHRS) on board the Hubble Space Telescope . Atomic data about the spectral line of 1307.50 Å and about the hyperfine components of the spectral lines of 1321.71 Å and 1908.64 Å were taken from different sources and used to analyse the isotopic abundance of thallium II in the star χ Lupi. From their results the authors concluded that the photosphere of the star presents an anomalous isotopic composition of Tl II . A study of the atomic parameters of Tl II and of the broadening by the Stark effect of its spectral lines (and therefore of the possible overlaps of these lines) can help to clarify the conclusions about the spectral abundance of Tl II in different stars. In this paper we present calculated values of the atomic transition probabilities and Stark broadening parameters for 49 spectral lines of Tl II obtained by using the Cowan code including core polarization effects and the Griem semiempirical approach. Theoretical values of radiative lifetimes for 11 levels (eight with experimental values in the bibliography) are calculated and compared with the experimental values in order to test the quality of our results. Theoretical trends of the Stark width and shift parameters versus the temperature for spectral lines of astrophysical interest are displayed. Trends of our calculated Stark width for the isoelectronic sequence Tl II –Pb III –Bi IV are also displayed.